(untitled) (Historia, 2021)
Many researchers and social science scholars have argued that since the advent of democracy in South Africa, or at least during President Zuma’s administration, the country has become synonymous with public protests. Such protests are often related to service delivery concerns. Jane Duncan’s Protest Nation: The Right to Protest in South Africa explores this issue. In understanding protest culture in South Africa, the first two chapters of the book elaborate extensively on the international trend which pertains to protest and state repression. Here, the author summarises the debates on the right to protest, as well as its limitations.